Issues of implementing computer integrated manufacturing (CIM) in medium size manufacturing industries / Nordiana Nordin - Nordin, Nordiana (2004)
Rapid growth of computer technology gives more advantage to manufacturing industries in order to improve and enhance their process and productivity. Computer technology is an integral element of Computer Integrated Manufacturing (CIM) concept. CIM is a production based information technology solutions, which are developed to assist manufacturing industries in terms of production process and quality control. CIM helps the medium industries to solve their production related problems. This research briefly discussed about the factors that influence the medium size manufacturing industries from not implementing the CIM. There are three factors that influence the medium size manufacturing from not implementing the CIM which consists of hindrances related to management factor, people factor, and technological and infrastructure. Hindrances related to management factors are expensive, few successes, not the right time, lack of knowledge and confuse with CIM. Hindrances related to people factor include the changes in work practices and fear of loss authority control. Besides that, this research also provides the benefits of CIM implementation in medium industries. Benefits from the implementation of CIM are increase business performance, increase profit, improve production management, save time motivate employees and reduce cost. Perhaps this research will give an awareness of CIM and guideline medium industries in order to implement CIM in their company